FPGA-based Adaptive Phase-shift Compensation Method for Electronic Instrument Transformers. Issue 7 (21st April 2017) - Huang, Can; Mei, Jun; Bu, Qiangsheng; Su, Lin
Abstract: Accurate and reliable instrument transformers play an important role in power system measurement and protection. This paper focuses on the phase accuracy of electronic instrument transformers and presents an adaptive phase-shift compensation method for measuring electronic current transformers. Different from the existing approaches in which the empirical evaluation and fixed phase-shift compensation are used, the proposed method measures the phase displacement in real-time and calibrates the corresponding phase error adaptively, with the aim of achieving high and reliable phase accuracy. In particular, several practical factors are considered in the design, such as the phase displacement composition, phase error uncertainty, synchronous mode diversity, and computational complexity and latency. The proposed method is developed in a field-programmable gate array platform with low-latency hardware implementation and further employed in a merging unit. Finally, the experimental results are provided to demonstrate the validity of the proposed method.